2021
DOI: 10.1088/1674-1056/ac1b89
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the beam quality in ionization injection by a tailoring gas profile*

Abstract: A new scheme is proposed to improve the electron beam quality of ionization-induced injection by tailoring gas profile in laser wakefield acceleration. Two-dimensional particle-in-cell simulations show that the ionization-induced injection mainly occurs in high-density stage and automatically truncates in low-density stage due to the decrease of the wakefield potential difference. The beam loading can be compensated by the elongated beam resulting from the density transition stage. The beam quality can be impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…[21,22] Using an externally injected electron bunch with 200 MeV, Caizergues et al have confirmed numerically the feasibility of phase-locked LWFA via particle-in-cell (PIC) simulations. However, this scheme is not self-consistently combined with the controlled injection process, such as density transition injection [25][26][27][28] or ionization injection, [29][30][31] which is widely used in normal LWFA. Due to a larger laser group velocity, the injection of electrons in phase-locked LWFA may be relatively difficult, which has not been studied, but is crucial for future experiments.…”
Section: Introductionmentioning
confidence: 99%
“…[21,22] Using an externally injected electron bunch with 200 MeV, Caizergues et al have confirmed numerically the feasibility of phase-locked LWFA via particle-in-cell (PIC) simulations. However, this scheme is not self-consistently combined with the controlled injection process, such as density transition injection [25][26][27][28] or ionization injection, [29][30][31] which is widely used in normal LWFA. Due to a larger laser group velocity, the injection of electrons in phase-locked LWFA may be relatively difficult, which has not been studied, but is crucial for future experiments.…”
Section: Introductionmentioning
confidence: 99%